2008
DOI: 10.1002/mnfr.200700308
|View full text |Cite
|
Sign up to set email alerts
|

Residues of deoxynivalenol (DON) in pig tissue after feeding mash or pellet diets containing low concentrations

Abstract: Residues of deoxynivalenol (DON) and its metabolite de-epoxy-DON (DOM) were analyzed in specimens of pigs fed diets containing 0, 25, and 50% contaminated wheat (2.5 mg DON/kg) fed as mash or pellets over the final growing period of 11 wk. Median DON concentrations decreased from bile > kidney > serum > liver = muscle, while DOM was only detected in bile and kidney. Maximum carry over rates were 0.0319 for kidney, 0.0064 for liver, and 0.0043 for muscle, demonstrating that the contribution of animal derived fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…For instance, in a recent study DON was detected in 98.7% of urine samples from adults in the United Kingdom [11]. In a recent study, pigs fed with low concentrations of DON showed toxin levels of up to 0.5 and 0.02 lM in bile and liver, respectively [15]. These levels are clearly below the 1 lM dose used in this study, which therefore may reflect worst case intake scenario rather than mean exposure.…”
Section: Discussionmentioning
confidence: 50%
“…For instance, in a recent study DON was detected in 98.7% of urine samples from adults in the United Kingdom [11]. In a recent study, pigs fed with low concentrations of DON showed toxin levels of up to 0.5 and 0.02 lM in bile and liver, respectively [15]. These levels are clearly below the 1 lM dose used in this study, which therefore may reflect worst case intake scenario rather than mean exposure.…”
Section: Discussionmentioning
confidence: 50%
“…Using the obtained results, the carry-over factor was calculated as the quotient of toxin concentration in the tissue (µg/kg) by toxin concentration in the diet (µg/kg), included as the total administered doses in the defined term experiment, according to previous researchers [38,43,44]…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study the concentrations of DON decreased from bile > kidney > serum > liver = muscle in an experiment, where pigs received diets containing 0%, 25% and 50% of contaminated wheat containing 2.5 mg DON/kg [43]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, metabolite de-epoxy-DON was detected only in liver (0–2.4 ng/g) (Doll et al ., 2008). The maximum recalculating factor (the sum of the DON and de-epoxy-DON in tissues divided by concentration of DON administered in the diet) was 0.0043 for muscle 0.0064 for liver and 0.0319 in the kidney (Doll et al ., 2008). These factors are very similar to those of other studies performed on pigs, which were fed with a diet contaminated by DON (6.68 mg/kg) for 12 weeks.…”
Section: Trichothecenes and Deoxynivalenolmentioning
confidence: 99%